1991
DOI: 10.1016/0022-3115(91)90291-e
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of welding irradiated materials

Abstract: Helium was implanted into solution-annealed (SA) 316 stainless steel, 20% cold-worked (CW) 316 stainless steel and titanium-modified Primary Candidate Alloy (PCA) through tritium decay to levels ranging from 0.18 to 256 appm.Full penetration welds were then made on helium-doped materials using gas tungsten arc welding (GTAW) under fully constrained conditions. Intergranular heat-affected zone (HAZ) cracking was observed in all of the materials containing greater than 1 appm He. Electron microscopy showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…As in the previous work (Ref. [2][3][4][5], this result continues to provide strong evidence for the use of the overlay technique for welding on helium. The GTA weave bead produced with the high heat parameters (Figure llb) had significant porosity in the weld metal compared to the GMA welds.…”
Section: Metallographic Examinationsupporting
confidence: 84%
See 1 more Smart Citation
“…As in the previous work (Ref. [2][3][4][5], this result continues to provide strong evidence for the use of the overlay technique for welding on helium. The GTA weave bead produced with the high heat parameters (Figure llb) had significant porosity in the weld metal compared to the GMA welds.…”
Section: Metallographic Examinationsupporting
confidence: 84%
“…Earlier work (Ref. [2][3][4][5][6][7] has shown that underbead cracking in helium charged stainless steel increases with an increase in helium concentration. The previous WSRC-TR-94-0449 work has also shown that a low-penetration weld overlay technique minimizes the adverse effects of helium on the weldability of stainless steel.…”
Section: Helium Concentration and Weld Typementioning
confidence: 99%
“…Al_plication of low-penetration gas metal arc (GMA) weld overlay techniques provided encouraging results by producing a pronounced reduction in cracking compared to the repair welds in the reactor tank. Reduction in helium embrittlement cracking has also been obtained by Lin et al [7,8] by cold working, precipitate addition, and by application of compressive stress during welding.…”
Section: Introductionmentioning
confidence: 83%
“…For the partial-penetration welds, intergranular HAZ cracking was observed for specimens with 105 appm helium. Lin and Chin (1991a) continued this research by observing the effects that modifying the alloy metallurgical condition had on GTAW welding of highly irradiated materials under full constraint. They used Type 316 stainless steel in the solution-annealed (SA) condition, with a 20% cold work (CW) condition, and a titanium modified condition referred to as the "primary candidate alloy" (PCA).…”
Section: International Fusion Program Research On Welding Of Highly Imentioning
confidence: 94%
“…The available literature contains numerous instances in which helium-induced cracking occurred during the welding of irradiated materials (Hall et al, 1978;Atkin, 1981;Kanne et al, 1995;Robinson, 1988;Goods and Karfs, 1991;Lin and Chin, 1991a;Van Osch et al, 1994;Fabritsiev and Van der Laan, 1996;and Watanabe et al, 1996). However, these reports lack consensus regarding the absolute minimum level of helium that induces cracking during welding operations.…”
Section: Problems Associated With Welding Irradiated Materials In Highmentioning
confidence: 99%